More on the pathogenesis of thrombotic thrombocytopenic purpura. Comment on “Acquired thrombotic thrombocytopenic purpura without detectable anti-ADAMTS13 antibodies: a possible underlying autoimmune mechanism” and on “The different faces of thrombotic thrombocytopenic purpura” - Flora Peyvandi (Haematologica)
Not available.